2006
DOI: 10.1016/j.stam.2006.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting and normal state properties of heavily hole-doped diamond synthesized at high pressure

Abstract: Diamonds, synthesized at high pressures and high temperatures in the presence of boron, are heavily hole-doped by incorporation of boron into the diamond lattice. These diamonds become superconducting below T c ¼ 2-9 K. Synthesis in the systems B-C and B 4 C-C at P ¼ 9 GPa and T ¼ 2500-2800 K result in formation of polycrystalline carbonado-like material, whereas synthesis from B-C-H gives small single crystals and intergrowth plates. Dense superconducting bodies can be prepared by compacting these single crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…This means that the long-range correlation is enhanced by increasing the concentration of impurities. This is consistent with the experimental observation that the T c of B-doped diamond increases with increasing the boron concentration [21,22,32,43]. Note that the impurity concentration n imp in our definition corresponds to the concentration of isolated substitutional boron acceptors.…”
Section: Doping Dependencesupporting
confidence: 90%
See 1 more Smart Citation
“…This means that the long-range correlation is enhanced by increasing the concentration of impurities. This is consistent with the experimental observation that the T c of B-doped diamond increases with increasing the boron concentration [21,22,32,43]. Note that the impurity concentration n imp in our definition corresponds to the concentration of isolated substitutional boron acceptors.…”
Section: Doping Dependencesupporting
confidence: 90%
“…Experimental studies have examined which scenario describes better the electronic structure of B-doped diamond [30][31][32][33][34][35][36][37]. We point out here that the two scenarios are not contradictory and can be described continuously.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies have been reported on synthesis and characterization of heavily boron-doped diamond [5][6][7][8][9]. Despite the gained insights, the relation between the local structure around boron dopants and physical properties of boron-doped diamond has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%